FROM OPPOSING SPACES TO FUZZY BOUNDARIES: EXPLORATION OF VISUAL IMAGES OF CYBERSPACE FROM THE PERSPECTIVE OF PRODUCTION DESIGN - Liu Guangquan; Azhari Md Hashim; Norman Yusoff, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
With the continuous expansion of art boundaries, Cyberspace has gradually shifted from philosophy and the computer field to visual design. More and more artists and designers are exploring different visual possibilities in Cyberspace. As the film has led the visual representation of Cyberspace in recent decades, the visual designer of film—production designers has become the main designer of the visual image of Cyberspace. During the decades of visual development of Cyberspace, this study selects three typical films in different eras for analysis, and it mainly explores the visual images of Cyberspace from the perspective of production design and considers that the development of visual images of Cyberspace has changed from opposing space to fuzzy boundaries.